Hybrid Lighting System Research in the Context of Increasing Efficiency; IOP Conference Series: Materials Science and Engineering; Vol. 463 : International Multi-Conference on Industrial Engineering and Modern technologies - Ovcharov A. T. Aleksandr Timofeevich (2018, 2018)
Title screen